Use of Spirulina platensis in place of vitamin mineral premix on the performance of broiler - Islam, KMS; Roy, P; Debi, MR; Kamruzzaman, M (Bangladesh Journal of Animal Science, 2021)
The experiment was conducted to compare the effects of different sources of Spirulina and vitamin mineral premix as feed additive on the growth performance of broiler. Two hundred day old broiler chicks (COBB-500) were divided into five groups such as T1-(Feed containing 0.30% Vitamin mineral premix+0.0% Spirulina), T2-(Feed containing 0.15% Vitamin mineral premix+0.15% Spirulina from China), T3-(Feed containing 0.0% Vitamin mineral premix+0.30% Spirulina from China), T4-(Feed containing 0.15% Vitamin mineral premix+0.15% Spirulina from Myanmar) and T5-(Feed containing 0.0% Vitamin mineral premix+0.30% Spirulina from Myanmar) having four replication in each group containing 10 birds/replication. The experiment was conducted for 28 days (Completely Randomized Design) with ad libitum feed and water. Live weight was numerically higher (P>0.05) in T4 in 4th weeks of age. Lower feed intake observed in T3 and T5 which was mainly 50% replacement of vitamin mineral premix by Spirulina. After end of the feeding trial feed conversion ratio (1.66) in control group was higher (P<0.05) than other groups (1.63, 1.64, 1.59 and 1.61 respectively in T2, T3, T4 and T5). Dressing percentage (63.12%), breast weight (21.22%) and thigh weight (8.54%) were higher (P<0.05) in T4 than all other groups. Concentration of total cholesterol in blood plasma (64.42mg/dl) and serum albumin (1.75g/dl) was lower (P<0.05) in T4. It could be concluded that Spirulina from Myanmar is better than China and 50% synthetic vitamin mineral premix could be replaced by using Spirulina from Myanmar for better growth of broiler. Bang. J. Anim. Sci. 2020. 49 (2): 151-158